NPSR1 polymorphisms influence recurrent abdominal pain in children: a population‐based study. Issue 10 (5th August 2014) - Henström, M.; Zucchelli, M.; Söderhäll, C.; Bergström, A.; Kere, J.; Melén, E.; Olén, O.; D'Amato, M.
Abstract Background Recurrent abdominal pain (RAP) occurs frequently among children and is one of the cardinal symptoms of functional gastrointestinal disorders (FGID). The mechanisms of visceral pain and RAP are not fully understood. A heritable component has been demonstrated and a few candidate genes proposed. NPSR1 encodes the receptor for neuropeptide S (NPS) and NPS‐NPSR1 signaling is involved in anxiety, inflammation, and nociception. NPSR1 polymorphisms are associated with asthma and chronic inflammatory diseases, but also with IBS‐related intermediate phenotypes such as colonic transit time and rectal sensory ratings. Here, we sought to determine whether genetic variability in the NPSR1 gene influences the presence of RAP in children. Methods Twenty‐eight single‐nucleotide polymorphisms (SNPs) in the NPSR1 gene region were successfully genotyped in 1744 children from the Swedish birth cohort BAMSE. Questionnaire information was used to define RAP as episodes of abdominal pain occurring at least once a month in 12‐year‐olds. Key Results The prevalence of RAP was 9% in BAMSE. Association with RAP was observed for seven NPSR1 SNPs, five of which withstood false discovery rate (FDR) correction for multiple testing (best p = 0.00054, OR: 1.55 for SNP rs2530566). The associated SNPs all map in a putative regulatory region upstream NPSR1, where they may exert their genetic effects through the modulation of gene expression. Conclusions & Inferences Genetic variation at the NPSR1 locus impacts children's predisposition to RAP episodes in a Swedish population.